ANALISIS SISTEM PENGELOLAAN LIMBAH PADA KEGIATAN BUDIDAYA IKAN DI BALAI BESAR PERIKANAN BUDIDAYA LAMPUNG LAUT, PESAWARAN, LAMPUNG SELATAN - Nur Fadilla Joda; Nurul Rahmadina Azzahra; Ni Komang Ayu Andita; Annisa Nurtiasari; Sumardi; Berti Yolida; Nadya Meriza (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Aquaculture activities generate various types of waste that can potentially degrade environmental quality if not properly managed. As an institution dedicated to the development of marine aquaculture, the Lampung Marine Aquaculture Center (BBPBL) has implemented a waste management system to preserve the aquatic environment. This study aims to examine the waste management system implemented in fish farming activities within the BBPBL Lampung facility, located in Pesawaran District, South Lampung. The approach used is qualitative descriptive, employing data collection techniques such as direct field observations, structured interviews, and a review of relevant documents. All collected data were then analyzed narratively to describe the types of waste generated and the sequence of their management processes. The findings revealed that the generated waste includes organic solid waste, wastewater, chemical residues, biological waste, residues from processing and post-harvest activities, as well as waste classified as hazardous and toxic materials. Wastewater treatment is carried out through a Wastewater Treatment Plant (WWTP), which includes the stages of collection, separation of contaminants, particle sedimentation, and regulation of chemical levels before the effluent is released back into the environment. The implementation of this system has proven effective in reducing the amount of pollutants such as dissolved solids, organic compounds, and chemical residues, thereby minimizing the risk of environmental pollution. Therefore, the implementation of an integrated wastewater management system at the Lampung Aquaculture Research and Development Center plays a strategic role in maintaining the quality of aquatic environments while supporting the sustainability of aquaculture operations.